Intervensi Dengan Pendekatan Cognitive Behavior Therapy untuk Mengurangi Diabetes-Related Distress pada Lanjut Usia dengan Penyakit Diabetes Mellitus Tipe 1 dan Tipe 2 - Chandradewi Kusristanti; Dharmayati Utoyo Lubis (Majalah Sainstekes, 2017)
Diabetes Mellitus (DM) is one of the most frequent disorders distributed globally. Many drugs or regimens being used, complication risks, and various factors may induce diabetes-related distress in DM patients. Many studies have found that the presence of diabetes-related distress may provide negative impacts to patients, physically and psychologically. In older  patients, the negative impacts may be worsened by the characteristics of older individuals. Having acknowledged those negative impacts to older DM patients, this study was aimed to learn the influence of cognitive behavior therapy approach to reduce diabetes-related distress in older DM patients. Two participants were selected in this study, both are older   adults with high level of diabetes-related distress. All participants experienced decreased level of diabetes-related distress from their participation in this intervention, as shown during interview, observation, and assessment using PAID (Problem Areas In Diabetes) questionnaire. All participants were able to practice the respective techniques. All participants also understand that the therapeutic success is determined by their independence and their willingness to change by practicing it in daily life.